Translating Radio Productions into Television Programmes: The Post-War Career of BBC Writer/Producer Nesta Pain. - Terkanian, Kate (Historical Journal of Film, Radio & Television, 2024)
When BBC Television resumed broadcasting in 1946, BBC radio still dominated the airwaves. However, within a decade, television had swiftly become the dominant medium. BBC radio producers from the Features Department were eager to try their hand at translating their audio productions into visual ones, although few were successful. BBC producer Nesta Pain ultimately remained in radio production, but she successfully translated some of her radio plays and productions into television programmes, including John Mortimer's The Dock Brief (1957), A Shaft of Light (1958), and Simon Raven's The Move Up Country (1961). As one of the few women, and one of the more successful BBC Features writer/producers of the 1940s and 1950s, Nesta Pain's approaches to translating her work to television and the obstacles she encountered trying to move from audio storytelling to a more visual media offers a glimpse into the difficulties radio producers faced in switching to new methods. This article discusses the successful, as well as challenging, moments she faced in attempting this transition and also explores how access to Pain's personal papers has greatly enhanced this understanding.